Nutritional Management for catch up growth in disease related & non–disease related malnutrition - Yoga Devaera (World Nutrition Journal, 2022)
Globally in 2020, 149 million children under 5 were estimated to be stunted, 45 million were estimated to be wasted according to WHO. Pediatric malnutrition (undernutrition) is estimated to contribute to approximately 45% of all child deaths globally.